Managerial Social Capital and Firm Risk - Al-Bataineh, Omar; Iqbal, Abdullah; King, Timothy (Palgrave Macmillan, 2025)
There has been recent interest in the role of social capital in the business environment, yet relatively little is known as to how social capital influences firm risk. We examine the relationship between managerial social capital (MSC), based on a structural definition of social capital (SC), and firm risk in the United Kingdom—a high social capital country. Using data on listed firms from 2006 to 2017, we find that MSC is associated with lower firm risk (idiosyncratic and total). Furthermore, employing corporate social responsibility (CSR), an alternative SC measure more aligned with a cognitive SC perspective, we show it is associated with higher idiosyncratic and total firm risks, consistent with a shareholder expense view. Although our main results are robust to endogeneity concerns, we also conduct numerous robustness tests, including industry-adjusted MSC measure, controlling for a firm’s risk management committee, controlling for board of directors’ national diversity mix, and using alternative risk estimations.
Keywords: Social capital; managers; risk; firms; Managerial Social Capital (MSC); Network theory; Firm Risk; Corporate Social Responsibility (CSR); fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|